2017
DOI: 10.4269/ajtmh.16-0754
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia felis Infection in Febrile Children, Ghana

Abstract: Abstract. Rickettsial infections are an underrecognized cause of febrile illness in sub-Saharan Africa. To evaluate the epidemiology and clinical features of rickettsial disease in pediatric patients in Ghana, we screened blood samples from febrile children aged less than 15 years presenting to an outpatient department in Ghana's Ashanti Region for the presence of rickettsial DNA. We detected Rickettsia felis in 7/470 (1.5%) blood samples, using two independent real-time polymerase chain reactions. No other Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
14
2
Order By: Relevance
“…Serum cytokines and chemokines were analyzed by bead-based LEGENDplex assay (BioLegend, London) from 23 febrile children < 15 years of age (age range 0–7 years, median: 2 years) with molecularly confirmed R. felis infection seen at St. Michael’s Hospital, Pramso, Ghana [ 3 ]. The detection limits of the LEGENDplex assay for the analyzed cytokines were as follows: bFGF (basic fibroblast growth factor: 5.03 pg/mL), G-CSF (granulocyte colony stimulating factor: 8.77 pg/mL), GM-CSF (granulocyte–macrophage colony stimulating factor: 9.44 pg/mL), IFNγ (3.08 pg/mL), IL-1ß (N/A), IL-2 (3.34 pg/mL), IL-4 (4.46 pg/mL), IL-5 (3.61 pg/mL), IL-6 (2.86 pg/mL), IL-8 (5.13 pg/mL), IL-9 (1.27 pg/mL), IL-10 (2.97 pg/mL), IL-12p70 (30.33 pg/mL), IL-13 (N/A), IL-17A (4.29 pg/mL), IL-17F (4.24 pg/mL), IL-21 (1.37 pg/mL), IL-22 (5.74 pg/mL), IP-10 (N/A), MCP-1 (N/A), MIP-1α (macrophage inflammatory protein-1α: 4.53 pg/mL), MIP-1β (macrophage inflammatory protein-1ß: 5.47 pg/mL), PDGF-BB (platelet derived growth factor: N/A), RANTES (regulated on activation, normal T cell expressed and secreted: N/A), TNFα (1.78 pg/mL), VEGF (vascular endothelial growth factor: 7.41 pg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum cytokines and chemokines were analyzed by bead-based LEGENDplex assay (BioLegend, London) from 23 febrile children < 15 years of age (age range 0–7 years, median: 2 years) with molecularly confirmed R. felis infection seen at St. Michael’s Hospital, Pramso, Ghana [ 3 ]. The detection limits of the LEGENDplex assay for the analyzed cytokines were as follows: bFGF (basic fibroblast growth factor: 5.03 pg/mL), G-CSF (granulocyte colony stimulating factor: 8.77 pg/mL), GM-CSF (granulocyte–macrophage colony stimulating factor: 9.44 pg/mL), IFNγ (3.08 pg/mL), IL-1ß (N/A), IL-2 (3.34 pg/mL), IL-4 (4.46 pg/mL), IL-5 (3.61 pg/mL), IL-6 (2.86 pg/mL), IL-8 (5.13 pg/mL), IL-9 (1.27 pg/mL), IL-10 (2.97 pg/mL), IL-12p70 (30.33 pg/mL), IL-13 (N/A), IL-17A (4.29 pg/mL), IL-17F (4.24 pg/mL), IL-21 (1.37 pg/mL), IL-22 (5.74 pg/mL), IP-10 (N/A), MCP-1 (N/A), MIP-1α (macrophage inflammatory protein-1α: 4.53 pg/mL), MIP-1β (macrophage inflammatory protein-1ß: 5.47 pg/mL), PDGF-BB (platelet derived growth factor: N/A), RANTES (regulated on activation, normal T cell expressed and secreted: N/A), TNFα (1.78 pg/mL), VEGF (vascular endothelial growth factor: 7.41 pg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In all of these samples R. felis was identified by sequencing of amplicons and BLAST analysis. Details on the molecular methods are described elsewhere [ 3 ]. Eight children had a P. falciparum co-infection as evidenced by thin and thick blood films.…”
Section: Methodsmentioning
confidence: 99%
“…Malaria and tick-borne diseases overlap in many African regions, therefore co-infections in Anopheles mosquitoes may be possible after successive or concomitant infectious blood meals on hosts carrying both micro-organisms. In African malaria-endemic regions, bacteria such as Rickettsia, Borrelia, Bartonella , and Coxiella are often the cause of misdiagnosed malaria-like fever cases (Mediannikov et al, 2013 ; Fotso Fotso and Drancourt, 2015 ; Mourembou et al, 2015 ; Angelakis et al, 2016 ; Cutler et al, 2016 ; Sothmann et al, 2017 ). In Sub-Saharan Africa, Borrelia- induced mortality rate is estimated at between 2 and 5% (Fotso Fotso and Drancourt, 2015 ), and in rural Senegal, the incidence of tick-borne relapsing fever is estimated to reach 11% (Fotso Fotso and Drancourt, 2015 ; Cutler et al, 2016 ).…”
Section: Malaria and Bacteria Co-infections In Mosquitoesmentioning
confidence: 99%
“…In Sub-Saharan Africa, Borrelia- induced mortality rate is estimated at between 2 and 5% (Fotso Fotso and Drancourt, 2015 ), and in rural Senegal, the incidence of tick-borne relapsing fever is estimated to reach 11% (Fotso Fotso and Drancourt, 2015 ; Cutler et al, 2016 ). Rickettsioses are a major public health problem in sub-Saharan Africa (Mediannikov et al, 2013 ; Mourembou et al, 2015 ; Sothmann et al, 2017 ). Rickettsia felis and Plasmodium co-infections were found in humans (Mediannikov et al, 2013 ) and recent studies showed that mosquitoes can readily transmit pathogenic bacteria such as R. felis and Francisella tularensis (Backman et al, 2015 ; Dieme et al, 2015 ).…”
Section: Malaria and Bacteria Co-infections In Mosquitoesmentioning
confidence: 99%
“…The mortality of murine typhus is very low (<1%) [13]. R. felis was identified as a potential cause of febrile illness in 1-15% of patients with fever from some African countries, e.g., Ghana and Senegal [14,15]. However, R. felis has also been found in blood samples of non-febrile control subjects, albeit at a significantly lower rate than in febrile patients [16,17].…”
Section: Introductionmentioning
confidence: 99%